Organizational Culture and Employee Performance: The Moderating Role of ASN Berakhlak Core Values in Statistics Indonesia of North Maluku Province - M. Djayusman; Fadhliah M. Alhadar; Muhammad Thahrim (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The demands of bureaucratic reform require civil servants to have professional, adaptive, and public service-oriented performance. This study aims to analyze the influence of organizational culture based on the Denison model, specifically the dimensions of involvement and adaptability, on employee performance at the Central Statistics Agency (BPS) of North Maluku Province with the Core Values ​​of ASN BerAKHLAK as a moderating variable. The study used a quantitative approach with a survey method on 157 civil servants selected through a proportional random sampling technique. Data were collected using a Likert-scale-based questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of SmartPLS 4.0. The results showed that involvement and adaptability had a positive and significant effect on employee performance. The Core Values ​​of ASN BerAKHLAK were shown to moderate the relationship between adaptability and employee performance in a negative direction, but did not significantly moderate the relationship between involvement and performance. These findings indicate that organizational culture plays an important role in improving civil servant performance, while internalization of BerAKHLAK values ​​can influence the employee adaptation process in a bureaucratic environment. This study enriches the study of organizational culture and bureaucratic reform in the public sector in Indonesia